Revit 2021: Essential Training for Structure (Imperial). - Wing, Eric (linkedin.com, 2020)
Find out how to use Revit 2021 for structural engineering. Learn to design foundations, add framing and rebar, and plot drawings—using examples in imperial units (inches and feet).